Field notes contributed by Babs Padelford and Loren Padelford, fall 1996 - Padelford, Babset al; Padelford, Lorenet al (1996)
List of birds and locations contributed by Babs Padelford and Loren Padelford. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed